PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS V SDN 161 PEKANBARU - Kartika Ayu Andina; Lazim N Lazim N; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was done because of the low learning outcomes of the V th grades of SDN 161 Pekanbaru. It can be seen from test semester on school from 22 students as criterion mastery (KKM) is 75. There are 5 students passed the test, and the are 17 students not passing the test on odd semeseter by having avarage grade is 54,86. To overcome the case, so researcher applyies cooperative learning model of index card match type which is this model to be able to grow students in understanding the concept of learning to be able to estabalish cooperation reletionship between students in answering question by watching index card in their hands. This research is a classroom action research. It is consinsting of the two cycle, each cycle consists of the meetings and only daily test at the end of research cycle. The subject of this research os the students of glade Va of elementry school of 161 Pekanbaru, after improvement of learning by using cooperative learning mode of index card type of student learning outcomes increase from score 54,86 increase in cycle 2 to 80,68 with the oncreasing percentage 27,59% increase again in cycle 2 to 80,68 with the increase of percentage 47,06% this applying of cooperative learning model of index card match type can improve learning result of social of students V grade of SDN 161 Pekanbaru.Key words : Cooperative learning Model, Index Card Match Type,Learning Outcomes Of Social